ナンキョク ニ オケル ムジン カンソク (II) ダイ20, 21ジ タイ ニ オケル システム ノ ガイヨウ ト ケッカ ノ ホウコク - 大畑, 哲夫; オオハタ, テツオ; 勝田, 豊; カツタ, ユタカ; Ohata, Tetsuo; Katsuta, Yutaka (1983)
P(論文) 第20次から第22次日本南極地域観測隊にかけて行われたPOLEX-South計画の一環として, 氷床上における無人気象観測を行った。日本隊の無人観測は, 第18次隊以来行われているが, その実績をふまえ, 風力発電機, 保温箱, 制御器等に改良を重ね, また新型の気象観測装置を製作した。電源として小型の12V200Wの風力発電機を採用し, 1台ないし4台並列で使用した。2次電池としては12V200Ahのトラック用の鉛蓄電池を用いた。保温箱は, 発泡スチロールを主体にし, 強度を高めるためにFRPによる加工をほどこした。制御器は, 過充電防止やヒーターの電源切り換えなどを行うために製作された。気象観測装置は, 風向風速, 気温, 雪温, 日射および気圧等のセンサー, およびカセットテープに記録を採る収録装置で構成された。設置した地点はY100およびH180であったが, 電源系統を中心にいくつかの問題が生じたため, かならずしも良好なデータはとれず, まだ改良の余地があることがわかった。採れたデータについては, 気象現象を面的に理解するのに役立つことがわかった。 As part of the POLEX-South program of the 20th to 22nd Japanese Antarctic Research Expedition (JARE) (1979-1981), unmanned meteorological observation was made on the Antarctic Ice Sheet. As JARE has been conducting unmanned observation since JARE-18,improvement of renewal of the parts of the system was made taking into account the previous works. As for electric source, wind generator of 12V200W was adopted and was set one or four in parallel. Insulation box was mainly made by styroform, and was strengthened by the use of FRP. Charge controller was made in order to prevent overcharge and control the heaters. Meteorological observation system was composed of sensors for wind speed and direction, air temperature, snow temperature, solar radiation and air pressure, and recording part using cassette tape recorder. This unmanned meteorological system was built at Y100 and H180. However, due mainly to troubles in the electric source part, this system did not function well continuously. There is still some room for improvement. The data taken seem to be helpful in understanding the areal meteorological phenomena. departmental bulletin paper